Respuesta :

Answer:

Step-by-step explanation:

"Find the values of x that satisfy 3x - 2x^2 = 7."  Please do not use " × " to represent a variable; " × " is an operator, the "multiply" operator.

Rearrange these three terms in descending order by powers of x:

-2x^2 + 3x - 7 = 0.   Here the coefficients are a = -2, b = 3 and c = -7, and so the discriminant of this quadratic is b^2-4ac, or 9 - 4(-2)(-7), or 9 - 56, or -47.

Because the discriminant is negative, we'll have two different complex roots here.  The quadratic formula becomes

       -3 ± i√47         -3 ± i√47

x = ----------------- = -------------------

        2(-2)                     -4